Cultural Transformation and Its Implications for Educational Aspirations in Bialo Village, Bulukumba Regency - Fifi Angraeni; Dimas Ario Sumilih (Gudang Jurnal Multidisiplin Ilmu, 2026)
This anthropological study explores the cultural transformations occurring within Bialo Village, Bulukumba Regency, and examines their direct implications for local educational aspirations. Utilizing a qualitative research methodology, data were gathered through in-depth interviews, participant observation, and focus group discussions with village elders, parents, and youth. Historically rooted in agrarian traditions and localized kinship structures, Bialo Village is currently experiencing significant socio-cultural shifts driven by modern digital connectivity, changing economic realities, and increased migration. The findings reveal that these cultural shifts have fundamentally reshaped how the community perceives the value of formal education. While traditional livelihoods once dictated a preference for early labor integration, modern cultural exposure has catalyzed a collective shift toward higher academic achievement. Formal schooling is increasingly viewed as a crucial vehicle for social mobility, economic security, and community empowerment. However, this transition also creates intergenerational tensions, as the younger generation's pursuit of modern academic credentials occasionally clashes with traditional family expectations and heritage preservation. Ultimately, this research highlights the dynamic intersection of cultural evolution and modern schooling, demonstrating how grassroots educational aspirations are continually renegotiated within a changing rural Indonesian landscape.